Crystallographic analysis of 1,2,3-trichloropropane biodegradation by the haloalkane dehalogenase DhaA31 - Lahoda, Maryna; Mesters, Jeroen R; Stsiapanava, Alena; Chaloupkova, Radka; Kuty, Michal; Damborsky, Jiri; Kuta Smatanova, Ivana (Acta crystallographica. Section D, Biological crystallography, 2014)
Haloalkane dehalogenases catalyze the hydrolytic cleavage of carbon-halogen bonds, which is a key step in the aerobic mineralization of many environmental pollutants. One important pollutant is the toxic and anthropogenic compound 1,2,3-trichloropropane (TCP). Rational design was combined with saturation mutagenesis to obtain the haloalkane dehalogenase variant DhaA31, which displays an increased catalytic activity towards TCP. Here, the 1.31 Å resolution crystal structure of substrate-free DhaA31, the 1.26 Å resolution structure of DhaA31 in complex with TCP and the 1.95 Å resolution structure of wild-type DhaA are reported. Crystals of the enzyme-substrate complex were successfully obtained by adding volatile TCP to the reservoir after crystallization at pH 6.5 and room temperature. Comparison of the substrate-free structure with that of the DhaA31 enzyme-substrate complex reveals that the nucleophilic Asp106 changes its conformation from an inactive to an active state during the catalytic cycle. The positions of three chloride ions found inside the active site of the enzyme indicate a possible pathway for halide release from the active site through the main tunnel. Comparison of the DhaA31 variant with wild-type DhaA revealed that the introduced substitutions reduce the volume and the solvent-accessibility of the active-site pocket.
Keywords: krystalografie rentgenová; Biodegradation, Environmental; Bacterial Proteins; Protein Structure, Tertiary; terciární struktura proteinů; biodegradation; látky znečišťující životní prostředí; propan; vapour-diffusion crystallization; Hydrolases; sekundární struktura proteinů; Protein Structure, Secondary; hydrolasy; Hydrolysis; Propane; Rhodococcus rhodochrous; molekulární modely; Crystallography, X-Ray; hydrolýza; Rhodococcus; Models, Molecular; alkyl-enzyme intermediate; mutageneze; Catalytic Domain; bakteriální proteiny; Environmental Pollutants; chlorinated compounds; Mutagenesis; katalytická doména; biodegradace